Yarlyk of Uzbek Khan Granted to the Franciscans of the Golden Horde in 1314: The Latin Text, Russian Translation, and Commentary - Roman Hautala (Золотоордынское обозрение)
The present article contains the Latin text, Russian translation, and commentary to the yarlyk of Uzbek khan (1312/13–1341). Uzbek khan granted this yarlyk to the Franciscans of the Golden Horde 20th March, 1314. Apparently, the original text of yarlyk was written in the Khwarezmian idiom of the Kipchak language. However, the original text of yarlyk has not been preserved as well as a number of other yarlyks of the Golden Horde khans, which survived only in the late Russian translation. Fortunately, this yarlyk was translated into Latin and, subsequently, this translation was rewritten by anonymous British copyist in the first half of the 14th century. Arthur Christopher Moule discovered this medieval copy of yarlyk along with several other Franciscan documents in one of the codices (D. Ii. 3.7.) stored in the Cambridge University Library. In 1924, Moule published the first and only edition of the yarlyk’s copy together with other Franciscan sources, provided with a thorough preface of Michael Bihl. The text of this Uzbek’s yarlyk have never been translated into modern languages. For this reason, the content of yarlyk has been known only to a narrow circle of specialists studying the Catholic missionary activity in the Mongol Empire. In turn, the scholars of the Golden Horde history, including researchers of the Jochid official documentation, have been unaware of this important legal document up to the present time. The content of Uzbek khan’s yarlyk points out that this document was based on the previous yarlyks of khan Mengu-Timur (1267–1282) and khan Tokhta (1291–1312). Thus, the content of yarlyk allows us to define the time of an emergence and future activities of the Franciscans in the territory of the Golden Horde. Furthermore, this information provide further evidence on the religious tolerance practice of the Jochid khans. In this context, the most significant is an indication of the Uzbek khan’s tolerant attitude toward Christians, despite the fact of his conversion to Islam.